2022
DOI: 10.1038/s41598-022-13312-z
|View full text |Cite
|
Sign up to set email alerts
|

Structural retinal changes in cerebral small vessel disease

Abstract: Cerebral small vessel disease (CSVD) is an important contributor to cognitive impairment and stroke. Previous research has suggested associations with alterations in single retinal layers. We have assessed changes of all individual retinal layers in CSVD using high-resolution optical coherence tomography (OCT) for the first time. Subjects with recent magnetic resonance imaging (MRI) underwent macular and peripapillary retinal imaging using OCT for this case–control study. Number and volume ratio index (WMRI) o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 61 publications
0
6
0
Order By: Relevance
“…In previous studies, we found that changes in RNFL thickness were closely related to stroke events, and some studies have also suggested the relationship between RNFL and GCC thickness changes and different imaging changes in CSVD ( Wang et al, 2014 ; Simsek, 2017 ; Langner et al, 2022 ). Since SRCP is mainly distributed in the RNFL and GCC layers, there should theoretically be consistency between the two changes.…”
Section: Discussionmentioning
confidence: 76%
“…In previous studies, we found that changes in RNFL thickness were closely related to stroke events, and some studies have also suggested the relationship between RNFL and GCC thickness changes and different imaging changes in CSVD ( Wang et al, 2014 ; Simsek, 2017 ; Langner et al, 2022 ). Since SRCP is mainly distributed in the RNFL and GCC layers, there should theoretically be consistency between the two changes.…”
Section: Discussionmentioning
confidence: 76%
“…There is mounting evidence that retinal biomarkers are related to the emergence of various CSVD imaging features, which is important for the increased risk of cognitive impairment ( 20 , 34 ). It has been reported that the CSVD burden was associated with a wider CRVE, a smaller AVR, and a higher incidence of vessel tortuosity ( 35 ).…”
Section: Discussionmentioning
confidence: 99%
“…RNFLD can be found in eyes with ischemic optic neuropathy, glaucomatous optic neuropathy, optic disc drusen, retinitis pigmentosa, retinal artery occlusion, contusion of the optic nerve, compression of pituitary tumor, visual pathway impairment, toxic optic neuropathy, and as a sequela of long-standing papilledema, optic neuritis, etc [1][2][3][4][5][6][7][8] . In addition, many risk factors, such as age, race, gender, blood pressure, blood glucose, smoke, etc., are known to increase an individual's chance of developing RNFLD [9][10][11] . RNFLD may result in vision loss.…”
Section: Introductionmentioning
confidence: 99%
“…Most of the studies used color fundus photographs to diagnose RNFLD. Previous research suggested that RNFLD play a significant role in the detection of various abnormal physical condition and diseases, such as diabetic mellitus, stroke, hypertension, Alzheimer's disease, multiple sclerosis, Parkinson's disease, pathologic myopia, etc [9,[12][13][14][15][16] . Some studies indicated that the prevalence of RNFLD in health examination participants is about 4.7%-5.4% [16][17] .…”
Section: Introductionmentioning
confidence: 99%